Zagrożenie terroryzmem oraz aspekt militarny w jego zwalczaniu - Dukiewicz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
In his article the author examines the problem of terrorist threats. Terrorism, playing an important role in the military environment, increasingly becomes the main threat in any conflict, influencing the functioning of the state. The methods of combating terrorism employed by NATO forces and the EU security system add another dimension to military operations. Experience from Iraq or Afghanistan indicates that in combating terrorism the key to victory lies primarily in intelligence information exchange as well as new operational techniques and procedures. Methods of fighting terrorism constantly evolve as a result of new trends and ways of operating used by terrorists.
Keywords: terroryzm; bezpieczeństwo międzynarodowe; zagrożenia bezpieczeństwa; służby specjalne; NATO